Longitudinal Force of Continuously Welded Rail on Suspension Bridge with Length Exceeding 1000 m. Issue 3 (3rd July 2019) - Yan, Bin; Zhang, Gaoxiang; Han, Zhongshu; Lou, Ping
Abstract: To study the distribution and regularity of the longitudinal force of continuously welded rail on a railway bridge, a railway suspension bridge with a span of (84 + 84 + 1092 + 84 + 84) m is taken as the engineering background. Considering the main cable, suspender, steel truss, orthotropic plate and adjacent bridge structure, a model of the interaction between the suspension bridge and four-line tracks is established. Distribution patterns of the longitudinal forces on the suspension railway bridge with length exceeding 1000 m are explored. On this basis, the influences of design parameters on the longitudinal force are discussed. The results show that the track expansion force at the bridge end can be greatly reduced after the installation of rail expansion devices at the end of the suspension bridge. As the vertical stiffness of the suspension bridge is relatively low, the deflection force instead of the expansion force becomes the control load. When the four-line loading is simultaneously loaded, the vertical rail displacement is 2.4 m, and the track deflection stress is up to 103.0 MPa. The relative displacement between the suspension bridge and track is about 10.8 mm owing to the vertical load, which could cause the ballast track to buckle.